Controlling a Switched Reluctance Motor with a Conventional Three-Phase Bridge Instead of Asymmetric H-Bridges - Haitao Sun; Ali Farzan Moghaddam; Abdalla Hussein Mohamed; Mohamed Nabil Ibrahim; Peter Sergeant; Alex Van den Bossche (Energies, 2018)
This paper proposes a new driving method for switched reluctance motors (SRMs) using the standard full-bridge inverter. In spite of changing the internal structure of an SRM, the proposed method uses an extra ring structure circuit to make it possible for the inverter to drive the SRM. Next to the standard converter, a controllable DC source is needed. With theoretical analysis and calculation, the reference value of the circulating current in the ring structure was determined and the new method was proven via simulation. A comparison was made with the conventional method for driving an SRM: the asymmetric H-bridges. Also, the current studies were then made to confirm that the SRM could be controlled without lowering the performance of the machine. Experimental verification was also made under different conditions, as well as comparison with the simulation results.